Trace elements content in cheese, cream and butter - Nina Bilandžić; Marija Sedak; Maja Đokić; Đurđica Božić; Božica Solomun Kolanović; Ivana Varenina (Mljekarstvo)
Trace elements were determined in five types of cheese, cream and butter using inductively coupled plasma-optical emission spectrometry. In cheese samples trace elements were measured as follows (mg/kg): Al 0.01-3.93, Co<0.005, Cr 0.005-1.66, Li 0.008-0.056, Mn 0.068-5.37, Mo 0.003-0.225, Ni 0.01-0.163 and Sr 0.085-3.49. There were significant differences considering the concentrations of Mn, Cr and Al (p<0.01, all) among the analysed dairy products. There were no significant differences in Sr, Mo, Ni and Li levels among products. The highest levels were found in following products (mg/kg): 4.23 Mn in semi-hard fat cheese, 2.43 Sr in cream cheese, 0.18 Mo in cream, 0.14 Ni and 0.028 Li in melted cheese, 1.13 Cr and 3.87 Al in butter. The trace element con¬centrations measured in cheeses and butter varied compared to the literature data. Concentrations of Al, Cr, Mn and Mo found in cheeses and Mn and Ni in butter were in line with contents reported in other countries. These results may demonstrate differences in production processes between countries. The estimated daily intakes (EDIs) calculated for Cr, Mn, Mo and Ni in cheeses showed a low contribution (0.59-3.38 %) to the reference values for the permitted daily exposure (PDE) for these elements. However, the high contribution of Al concentrations (56 and 124 %) to PTWI (provisional maximum tolerable daily intake) calculated in fresh and melted cheese may pose a health risk to consumers.